Financing investment projects in the IT sector of the Russian economy - G. A. Tarasov (Вестник университета)
The purpose of the article is to analyze the specifics of financing investment projects in the IT sector of the Russian economy. As part of the paper’s research objectives systemic aspects and peculiarities of investment in the IT sphere, state of the Russian IT market, and trends in its development have been considered. IT investment types and characteristics have been analyzed. Research methods include data systematization and generalization on the topics of modern research on the peculiarities of financing investment projects in the IT sector of the Russian economy. The developed target mechanism allows to consider system aspects of investment and improve validity of the most effective option choice for the IT sphere, which is a new scientific result obtained by the author. Based on the proposed sequence of using the target mechanism, it is possible to develop effective algorithms for decision-making on investment in the IT sphere.